Solar concentrating modules with louvered heliostats emerging research and opportunities - Strebkov, D. S. (Dmitriĭ Semënovich), 1937- (Advances in environmental engineering and green technologies (AEEGT) book series., 2021)
"This book explores current trends in the development of energy supply systems associated with the use of concentrated solar radiation"--